Development of a new analytical method for determination of acetylsalicylic and salicylic acids in tablets by reversed phase liquid chromatography - José Luiz Neves de Aguiar; Katia Christina Leandro; Shirley de Mello Pereira Abrantes; André Luis Mazzei Albert (Universidade de São Paulo, 2009)
Acetylsalicylic acid (AAS) is a drug utilized as analgesic, anti-inflammatory, and antipyretic medication, available worldwide and commonly used in Brazil. Salicylic acid (AS) is a precursor in AAS synthesis and is also produced during its degradation. The official United States Pharmacopoeia (USP) suggests the determination of these drugs by high performance liquid chromatography (HPLC), with ultraviolet detection, but this method has neither a high sensitivity (S AAS=0.12 mAbs/(μg/mL) and S AS=0.48 mAbs/(μg/mL)) nor resolution (Rs=1.61). The purpose of this study was to develop a new more adequate, accurate method by liquid phase chromatography than the current official methodology, and to use this new method in the determination of the tenors of acetylsalicylic, as of salicylic acids in tablets. The parameters of the chromatographic system for both the AAS and AS were satisfactory. Selectivity was verified by absorption spectra comparison in the ultraviolet (UV) range, during and after substance retention time. The linear range for AAS was 0.21 to 0.39 mg/mL, and that for AS was 6.3 to 11.7 μg/mL. The correlation coefficients (r) of the analytical curves of AAS and AS were 0.9995 and 0.9988, respectively; and the detection and quantification limits for the AS were 0.23 and 0.69 μg/mL. The sensitivity (S AAS=1.88 mAbs/(μg/mL) and S AS=1.84 mAbs/(μg/mL)) and the resolution (Rs =5.06) show the improvement obtained using this method over that described by the USP. O ácido acetilsalicílico (AAS) é um fármaco utilizado como analgésico, antiinflamatório, antipirético, sendo amplamente comercializado e consumido no Brasil e no mundo. Como precursor de sua síntese utiliza-se o ácido salicílico (AS) que também é produzido através de sua degradação. A metodologia oficial da Farmacopéia Americana (USP) preconiza a determinação destes fármacos por cromatografia líquida de alta eficiência (CLAE) com detecção por ultravioleta, mas este método não possui boa sensibilidade (S AAS=0,12 mAbs/(μg/mL) e S AS=0,48 mAbs/(μg/mL)) e resolução (Rs =1,61). O objetivo deste trabalho, visando a melhor adequação do sistema cromatográfico em relação à metodologia oficial, foi o desenvolvimento e otimização de um novo método por cromatografia em fase líquida para determinar os teores tanto do ácido acetilsalicílico quanto do salicílico em comprimidos. Os parâmetros da adequação do sistema cromatográfico para o AAS e para o AS foram satisfatórios. A seletividade foi verificada por comparações dos espectros de absorção no ultravioleta (UV) antes, durante e depois do tempo de retenção da substância. A faixa linear de trabalho para o AAS foi de 0,21 a 0,39 mg/mL e a do AS foi de 6,3 a 11,7 μg/mL. Os coeficientes de correlação (r) das curvas analíticas do AAS e do AS foram de 0,9995 e 0,9988, respectivamente e os limites de detecção e quantificação para o AS foram 0,23 e 0,69 μg/mL. A sensibilidade (S AAS=1,88 mAbs/(μg/mL) e S AS=1,84 mAbs/(μg/mL)) e a resolução (Rs=5,06) atestam a melhoria em relação ao método descrito na USP.